Identification of a Hierarchy of Multipotent Hematopoietic Progenitors in Human Cord Blood - Majeti, Ravindra (2007)
Mouse hematopoiesis is initiated by long-term hematopoietic stem cells (HSC) that differentiate into a series of multipotent progenitors that exhibit progressively diminished self-renewal ability. In human hematopoiesis, populations enriched for HSC activity have been identified, as have downstream lineage-committed progenitors, but multipotent progenitor activity has not been uniquely isolated. Previous reports indicate that human HSC are enriched in Lin-CD34+CD38- cord blood and bone marrow and express CD90. We demonstrate that the Lin-CD34+CD38- fraction of cord blood and bone marrow can be subdivided into three subpopulations: CD90+CD45RA-, CD90-CD45RA-, and CD90-CD45RA+. Utilizing in vivo transplantation studies and complementary in vitro assays, we demonstrate that the Lin-CD34+CD38-CD90+CD45RA- cord blood fraction contains HSC, and isolate this activity to as few as 10 purified cells. Furthermore, we report the first prospective isolation of a population of candidate human multipotent progenitors, Lin-CD34+CD38-CD90-CD45RA- cord blood.